Production of xylo-oligosaccharides by immobilized-stabilized derivatives of endo-xylanase from Streptomyces halstedii - Aragon, Caio C. [UNESP]; Mateo, Cesar; Ruiz-Matute, Ana I.; Corzo, Nieves; Fernandez-Lorente, Gloria; Sevillano, Laura; Díaz, Margarita; Monti, Rubens [UNESP]; Santamaría, Ramón I.; Guisan, Jose M. (Elsevier, 2013)
An endoxylanase from Streptomyces halstedii was stabilized by multipoint covalent immobilization on glyoxyl-agarose supports. The immobilized enzyme derivatives preserved 65% of the catalytic activity corresponding to the one of soluble enzyme that had been immobilized. These immobilized derivatives were 200 times more stable 200 times more stable than the one-point covalently immobilized derivative in experiments involving thermal inactivation at 60 °C. The activity and stability of the immobilized enzyme was higher at pH 5.0 than at pH 7.0. The optimal temperature for xylan hydrolysis was 10 °C higher for the stabilized derivative than for the non-stabilized derivative. On the other hand, the highest loading capacity of activated 10% agarose gels was 75 mg of enzyme per mL of support. To prevent diffusional limitations, low loaded derivatives (containing 0.2 mg of enzyme per mL of support) were used to study the hydrolysis of xylan at high concentration (close to 1% (w/v)). 80% of the reducing sugars were released after 3 h at 55 °C. After 80% of enzymatic hydrolysis, a mixture of small xylo-oligosaccharides was obtained (from xylobiose to xylohexose) with a high percentage of xylobiose and minimal amounts of xylose. The immobilized-stabilized derivatives were used for 10 reaction cycles with no loss of catalytic activity. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Hydrolysis of xylan; Multipoint covalent immobilization of enzymes; Production of xylo-oligosaccharides; Thermo-stabilization of endoxylanases; Covalent immobilization; Immobilized enzyme; Loading capacities; Optimal temperature; Thermal inactivation; Xylan hydrolysis; Xylooligosaccharides; Bacteria; Catalyst activity; Enzymatic hydrolysis; pH effects; Enzyme immobilization; Streptomyces; Streptomyces halstedii